2022
DOI: 10.37349/etat.2022.00115
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell-targeting chemokines inhibit colorectal cancer progression

Abstract: Aim: Recent progress in cancer immunotherapy has shown its promise and prompted researchers to develop novel therapeutic strategies. Dendritic cells (DCs) are professional antigen-presenting cells crucial for initiating adaptive anti-tumor immunity, therefore a promising target for cancer treatment. Here, anti-tumor activities of DC-targeting chemokines were explored in murine colorectal tumor models. Methods: The correlation of chemokine messenger RNA (mRNA) expression with DC markers was analyzed using The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Accordingly, CCL3 activities that hamper cancer growth have been also demonstrated. They are attributed to the chemokine impact on various populations of anti-tumor immune cells, including upregulating the number of CD45 + leukocytes in the tumor [39] and recruiting cytotoxic T and NK cells into the tumor microenvironment (TME) [40,41]. CCL4 is also upregulated in CRC [25,30] and its systematic concentrations are elevated [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, CCL3 activities that hamper cancer growth have been also demonstrated. They are attributed to the chemokine impact on various populations of anti-tumor immune cells, including upregulating the number of CD45 + leukocytes in the tumor [39] and recruiting cytotoxic T and NK cells into the tumor microenvironment (TME) [40,41]. CCL4 is also upregulated in CRC [25,30] and its systematic concentrations are elevated [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Still, some authors have reported an upregulation of CCL19 at advanced CRC stages [25,46]. Others, in turn, have linked the chemokine overexpression with better prognosis, given its ability to recruit antitumor immune cells into TME [39,56]. Their presence translates into suppressed tumor growth [39,57], linked with an upregulation of IFNγ and IL-12 secretion [57] and inhibition of angiogenesis [54].…”
Section: Discussionmentioning
confidence: 99%